TRIM28 maintains genome imprints and regulates development of porcine SCNT embryos. Issue 4 (April 2021) - Zhai, Yanhui; Zhang, Meng; An, Xinglan; Zhang, Sheng; Kong, Xiangjie; Li, Qi; Yu, Hao; Dai, Xiangpeng; Li, Ziyi
Abstract : Pre-implantation embryos undergo genome-wide DNA demethylation, however certain regions, like imprinted loci remain methylated. Further, the mechanisms ensuring demethylation resistance by TRIM28 in epigenetic reprogramming remain poorly understood. Here, TRIM28 was knocked down in oocytes, and its effects on porcine somatic cell nuclear transfer (SCNT) embryo development was examined. Our results showed that SCNT embryos constructed from TRIM28 knockdown oocytes had significantly lower cleavage (53.9 ± 3.4% vs 64.8 ± 2.7%) and blastocyst rates (12.1 ± 4.3% vs 19.8 ± 1.9%) than control-SCNT embryos. The DNA methylation levels at the promoter regions of the imprinting gene IGF2 and H19 were significantly decreased in the 4-cell stage, and the transcript abundance of other imprinting gene was substantially increased. We also identified an aberrant two-fold decrease in the expression of CXXC1and H3K4me3 methyltransferase (ASH2L and MLL2), and the signal intensity of H3K4me3 had a transient drop in SCNT 2-cell embryos. Our results indicated that maternal TRIM28 knockdown disrupted the genome imprints and caused epigenetic variability in H3K4me3 levels, which blocked the transcription activity of zygote genes and affected the normal developmental progression of porcine SCNT embryos.